2020
DOI: 10.1371/journal.pone.0236955
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing vaccination coverage among children age 12–23 months in Afghanistan: Analysis of the 2015 Demographic and Health Survey

Abstract: Background Childhood vaccination plays a key role in reducing morbidity and mortality from vaccine-preventable diseases. Numerous studies have assessed the influence of demographic and socioeconomic factors on child immunization around the world. There are few such studies in Afghanistan, however. Therefore, this study aimed to identify factors influencing vaccination status among children age 12-23 months in Afghanistan. Materials and methods Nationally representative data from the 2015 Afghanistan Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 20 publications
12
34
0
1
Order By: Relevance
“…Children living in urban areas have been reported to have better vaccination status compared with their rural areas. This finding supports studies in Ethiopia [ 12 ] and Afghanistan [ 11 ], total vaccination level in urban residence was always higher than in rural residence. This might be due to the fact that urban areas have better access to health facilities and health care practitioners than rural areas.…”
Section: Discussionsupporting
confidence: 91%
“…Children living in urban areas have been reported to have better vaccination status compared with their rural areas. This finding supports studies in Ethiopia [ 12 ] and Afghanistan [ 11 ], total vaccination level in urban residence was always higher than in rural residence. This might be due to the fact that urban areas have better access to health facilities and health care practitioners than rural areas.…”
Section: Discussionsupporting
confidence: 91%
“…However, being children to the category of richest household was not statistical signi cant, this may be due to small observations. These results seems in line with previous studies (20,22). These relationships may partly be explained by; Women in higher territory of wealth are likely to empowered and less likely to confront challenge of transportation fee to take their child to vaccination site.…”
Section: Discussionsupporting
confidence: 92%
“…The current study found that children born from mothers who had at least four ANC visits are 10 folds more likely to be fully vaccinated than not vaccinated compared to no ANC visits, and had ve times higher relative risk of partially vaccinated than not vaccinated children compared to who had no visits. This nding is consistent with research done in Ethiopia (18), Bangladesh (19), Afghanistan (20) and Senegal (13). The same pattern of association was observed among women who had one to three antenatal care visits.…”
Section: Discussionsupporting
confidence: 91%
“…11 In Afghanistan with its already low general coverage of vaccination, that is, 39%, people's willingness and hesitancy toward COVID-19 vaccine is of particular importance. 13 To make sure the vaccination efforts succeed and the coverage required to reach herd immunity will be achieved, policy makers need to be informed about public willingness to take the COVID-19 vaccine. Therefore, this study aims to evaluate the willingness and hesitancy of Afghanistan population toward the COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%